Association between paraoxonase 1 (PON1) enzyme activity, PON1 C(−107)T polymorphism, nutritional status, and lipid profile in children. Issue 1 (December 2016) - Uliano, Gabriela; Muniz, Ludmila; Barros, Carlos; Schneider, Augusto; Valle, Sandra
Abstract Background Paraoxonase 1 (PON1) is an enzyme that possesses anti-atherogenic and anti-inflammatory properties with serum levels determined by genetic and exogenous factors. Lower serum PON1 arylesterase activity is associated to metabolic alterations related to childhood overweight and onset and/or development of diabetes and CVD later in life. However, data on the relationship between genetic PON1 polymorphisms and nutritional status as well as lipid profile in children are limited. To investigate the distribution of the C(−107)T PON1 gene polymorphism and its relation with serum PON1 enzyme activity, nutritional status and lipid profile in children. Methods A cross-sectional study was performed including 73 children aged 5 to 7 years who attended public pediatric clinics. PON1 C(−107)T, arylesterase activity, body mass index for the age, and serum lipid profile were evaluated. Results PON1 activity was higher in overweight children compared to the normal weight ones (p = 0.02). The genotypic frequency did not differ between the two groups (p > 0.05). Carriers ofCC genotype had higher enzyme activity thanT allele carriers, and this difference was greater among normal weight children. HDL levels were higher among normal weight children carrying CC genotype, compared to those carrying the T allele (p < 0.01). Conclusion The PON1 C(−107)T polymorphism is associated with higher serum enzyme activity in children, as observed previously in adults. In addition, this polymorphism also shows association to higher high density lipoprotein (HDL) levels and serum PON1 arylesterase activity in the normal weight children studied.